The Illustrated Library of Nature : An Encyclopedia of Natural History and Ecology. Vol. 1 - Editorial Consultant by Meyer, Alfred (New York H.S. Stuttman, 1971)
Includes articles and photographs on varied aspects of natural history and ecology arranged under such topical areas as "Animal World," "Desert Life, " and "Plants."
Include Color Illustration
Keywords: Zoology -- Animals